Common wart/Solitary papular angiokeratoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Viral common wart is often characterized by red brownish dots due to hemorrhages of the dilated small vessels of the dermal papillae; the dots are a clue to the diagnosis in the doubtful cases. Solitary papular angiokeratoma is characterized by both hyperkeratosis and dilated vessel in the papillar dermis. Due to the presence in both the disorders of hyperkeratosis and vessel component they need to be differentiated in some cases.